A Critical Discourse Analysis of CNBC Indonesia and CNN Indonesia on Russia’s Invasions of Ukraine: A Socio-Cultural Dimension (International Journal of Linguistics and Indigenous Culture, 2025)
This study aims to critically examine how CNBC News and CNN News Indonesia portrayed Russia's military actions in Ukraine through the lens of Fairclough's socio-cultural dimension of Critical Discourse Analysis (CDA), specifically focusing on political, economic, and cultural perspectives. Using a qualitative methodology, the analysis of selected articles from both media outlets between February and August 2022 revealed that both media outlets propagated justifications for Russia’s military actions, citing geopolitical and national security concerns. For instance, the media described Russia’s actions as defensive responses to NATO's affiliations with the United States and perceived economic threats related to food and energy security. However, the analysis also uncovered differences in framing economic impacts. CNN News Indonesia highlighted immediate humanitarian and economic crises, whereas CNBC News emphasized long-term global economic implications. This research underscores the media’s influential role in shaping public perceptions of geopolitical conflicts in Indonesia.